Chapter Disegni di Cesare e Pietro Dandini dalla raccolta Dandini-Targioni Tozzetti - Benassai, Silvia (Studi e saggi, 2020)
The essay concerns two drawings by the Florentine baroque painters Cesare and Pietro Dandini, coming from the Dandini-Targioni Tozzetti collection. The naturalist Giovanni Targioni Tozzetti (1712-1783), consort of Maria Brigida, daughter of Ottaviano Dandini, brought together the impressive set of drawings belonging to the Dandini family, which were divided into twenty volumes, probably dismembered in the Nineteenth century. The paper presents two drawings which belonged to that collection: a sheet in sanguine by Cesare Dandini depicting a male figure, and a drawing by Pier Dandini depicting The glory of Saint Verdiana, a preparatory study for an altarpiece that was part of a series of large canvases executed by Pier Dandini between 1706 and 1710 for the basilica of Santa Trinita in Florence.